Beliefs about family policy among US mothers in publicly-subsidised housing: collective responsibility or individual self-sufficiency. (1st October 2019) - Kane, Emily W.
Abstract : In the context of critiques of welfare policy in the USA, I explore how mothers living in public housing balance notions of individual and collective responsibility for families struggling with poverty. Participants recognise collective responsibility at the institutional level and prefer inclusive approaches to public assistance policy. But the hegemony of individualism in the culture and in the framing of their specific programme pulls them toward the rhetoric of personal responsibility and a punitive, market-based logic of individual choice. This, in turn, obscures the gendered and classed structures reinforced by neoliberal policy's emphasis on privatised market forces and personal responsibility.